Some personality traits among memorizers of the Holy Qur’an and secondary school students in the city of Bani Walid (Journal of Human Sciences, 2023)
The current research aims to identify some personality traits among memorizers of the Holy Qur’an and secondary school students in the city of Bani Walid. In order to achieve the goal of the research, the researcher used the descriptive approach as a research approach. The study population included all students enrolled in the centers for memorizing the Holy Qur’an in the Al-Quds Mosque and the Martyr’s Mosque. It also included All students enrolled in Afaq Al-Mustaqbal School for Secondary Education and Al-Barq Al-Khatif School for Secondary Education, and the study sample reached (80) students, including (40) students from the Qur’an memorization and (40) students from the secondary school in Bani Walid. The sample was selected by a simple random method of ( 20) A student from each secondary school and center of the Holy Qur’an memorization attached to the Martyr’s Mosque and Al-Quds Mosque affiliated with the General Authority for Endowments and the secondary schools represented by the Lightning Lightning School and the Future Horizons School affiliated with the Basic Education Supervision Bani Walid. The researcher used a tool prepared by H.J.Eysneck (1968) and Arabized it. (Salah Abu Nahia 1989). This scale includes (90) items distributed over (4) dimensions: Extroversion - Introversion - Neuroticism - Psychoticism - Lying (social attractiveness). The researcher reached a number of results, the most important of which are: The answer to the first question was the most important personal reasons in the first three results (ease of giving in to bad companions (80.2%), students’ lack of interest in school (76.2%), and lack of ability to learn (75.8%). As for the results of the second question, the first three on the most important family reasons are (the family’s continuous movements and frequent departures, at a rate of (80.0%) - neglect and family disintegration, at a rate of (71.4%). We find that the results of the third question, which are the school reasons for dropping out (the inferiority view of mainstream education, at a rate of (75.8%). School violence (physical and moral) at a rate of (69.6%) - and difficulty of the curriculum at a rate of (62.4%)